The Relationship Between Mother's Knowledge And The Triple Elimination Examination Of Pregnant Women At Puskesmas Sei Agul District West Medan, Medan City Year 2022 - Herlia Sumardha Nasution (Sean Institute, 2023)
Pregnancy is a normal reproductive process experienced by the mother. Pregnant women need to pay attention to various conditions, such as transmission of HIV/AIDS, hepatitis and syphilis. Efforts are needed to break the chain of transmission of the disease with a triple elimination examination. Knowledge of pregnant women about triple elimination examination needs to be improved. This study aims to determine the relationship between maternal knowledge and Triple Elimination examination of pregnant women at the Sei Agul Health Center, Medan Barat District, Medan City in 2022. This research is a descriptive correlation study with a cross sectional approach. This research was carried out from 13 September 2022 to 24 September 2022. The population was 230 people. Sampling using accidental sampling with a total sample of 35 people. The analysis used univariate and bivariate analysis using the chi-square test statistic. The results of the study found that the majority of mothers' knowledge at the Sei Agul Health Center was good and the Triple Elimination Examination of pregnant women at the Sei Agul Health Center was mostly doing examinations. Based on the results of the chi-square test, it was found that the value of p = 0.001 <0.05, there is a relationship between maternal knowledge and Triple Elimination examination of pregnant women at the Sei Agul Health Center, Medan Barat District, Medan City in 2022. The conclusion in this study is that there is a relationship between maternal knowledge and Triple Elimination examination of pregnant women at the Sei Agul Health Center, Medan Barat District, Medan City in 2022. Suggestions in this study, the Sei Agul Health Center, Medan Barat District, continue to activate optimizing the role of midwives and health workers to optimize the willingness of mothers to carry out triple elimination examinations by increasing the knowledge of pregnant women.